Physical Home Food Environment And Its Correlation With Iron And Vitamin C Intake Of Children In Pejagalan - Adhelia Niantiara Putri; Dian Novita Chandra; Luh Ade Ari Wiradnyani; Alfi Rahma Putri; Fitya Safira Birahmatika; Dwi Nastiti Iswarawanti; Lestari Octavia; Hera Nurlita (Universitas Airlangga, 2022)
Despite the fact that Indonesia has established nutrition and health measures to prevent childhood malnutrition, more than 70% of children aged 2 to 5 consume less iron than the Indonesian dietary recommendations. Iron deficiency harms children's cognitive and motor development, increase morbidity. Ascorbic acid prevents stomach iron accumulation, inhibiting nonheme absorption. Iron-deficient kids don't eat enough. 65 to 72% of children's daily calories are consumed at home, hence the environment is crucial. The purpose of this study is to see if the iron and vitamin C consumption of children aged 2 to 6 in Pejagalan, North Jakarta, is related to their eating environment. There were 191 samples examined. To assess children's intake, 2x24h food recalls were performed. A modified version of the NHANES CBQ was used to assess the home food environment. For each response, 1 signified